Diabetes pathogenic mechanisms and potential new therapies based upon a novel target called TXNIP. Issue 2 (April 2018) - Thielen, Lance; Shalev, Anath
Abstract : Purpose of review: Thioredoxin-interacting protein has emerged as a major factor regulating pancreatic β-cell dysfunction and death, key processes in the pathogenesis of type 1 and type 2 diabetes. Accumulating evidence based on basic, preclinical, and retrospective epidemiological research suggests that TXNIP represents a promising therapeutic target for diabetes. The present review is aimed at providing an update regarding these developments. Recent findings: TXNIP has been shown to be induced by glucose and increased in diabetes and to promote β-cell apoptosis, whereas TXNIP deletion protected against diabetes. More recently, TXNIP inhibition has also been found to promote insulin production and glucagon-like peptide 1 signaling via regulation of a microRNA. β-Cell TXNIP expression itself was found to be regulated by hypoglycemic agents, carbohydrate-response-element-binding protein, and cytosolic calcium or the calcium channel blocker, verapamil. Retrospective studies now further suggest that verapamil use might be associated with a lower incidence of type 2 diabetes in humans. Summary: TXNIP has emerged as a key factor in the regulation of functional β-cell mass and TXNIP inhibition has shown beneficial effects in a variety of studies. Thus, the inhibition of TXNIP may provide a novel approach to the treatment of diabetes.